Ustekinumab in Paediatric Patients with Moderately to Severely Active Crohn's Disease: Pharmacokinetics, Safety, and Efficacy Results from UniStar, a Phase 1 Study. (26th May 2021) - Rosh, Joel R; Turner, Dan; Griffiths, Anne; Cohen, Stanley A; Jacobstein, Douglas; Adedokun, Omoniyi J; Padgett, Lakshmi; Terry, Natalie A; O'Brien, Christopher; Hyams, Jeffrey S
Abstract: Background and Aims: The objective was to evaluate the pharmacokinetics, safety/tolerability, and efficacy of ustekinumab in children with moderately to severely active Crohn's disease. Methods: In this Phase 1, multicentre, 16-week, double-blind, induction dose-ranging study [NCT02968108], patients aged 2‐<18 years [body weight ≥10 kg] were randomised [1:1] to one of two weight range-based intravenous induction doses: 130 mg vs 390 mg in patients ≥40kg and 3 mg/kg vs 9 mg/kg in patients <40kg. At Week 8, all patients received a single subcutaneous ustekinumab maintenance dose of 90 mg in patients ≥40kg or 2 mg/kg in patients <40kg. Results: A total of 44 patients were randomised and treated with ustekinumab [ n = 23 lower dose; n = 21 higher dose]; median [interquartile range] age was 13.0 [12–16] years. Pharmacokinetics were similar to those in adults with Crohn's disease. However, serum ustekinumab concentrations were lower among those with body weight <40 kg compared with patients ≥40 kg and the reference Phase 3 adult population. Through Week 16, 73% of patients reported ≥1 adverse event [82.6% lower vs 62% higher dose]; two discontinued due to adverse events [one in each group]. Serious adverse events occurred in 16% [26% lower, 5% higher dose], with Crohn's disease exacerbation being the most frequent. At Week 16, 22%/29% [lower/higher dose] achieved clinical remission [Paediatric Crohn's Disease Activity Index ≤10]. Conclusions: The pharmacokinetics/safety profiles were generally consistent with those observed in adults with Crohn's disease. These results suggest a different dosing regimen may be required for patients <40 kg from that employed in this study; additional pharmacokinetic analyses may be needed in this population.